Prosocial Orientation of Russians During the COVID-19 Pandemic: Caring for Others and Yourself - Kislyakov, Pavel A.; Shmeleva, Elena A. (Frontiers in Psychology, 2021)
To mitigate the potentially devastating effects of the COVID-19 pandemic, it is vital to identify psychosocial and moral resources. The care, preservation, protection, and well-being of social communities are attributes of prosocial behavior that can be such a resource. The purpose of the study is to identify the features of prosocial orientation of Russian youth during the COVID-19 pandemic, as well as to identify strategies for prosocial behavior during the COVID-19 pandemic. The sample consisted of 447 people. The study was conducted in May 2020 in the form of an online survey of subjects using Google Forms (“Moral Foundations Questionnaire method” and “Portrait Values Questionnaire”). The research made it possible to establish that Russians were dominated by norms of care, fairness, purity; values of benevolence-universalism, security, and self-direction. During the COVID-19 pandemic, the prosocial orientation of Russians may manifest itself in the following behavioral strategies: proactive prosocial strategy of “caring for others” (true altruism, expressed in forms of volunteering, helping a stranger, and charity despite the risk of contracting a coronavirus infection); egoistic strategy of prosocial behavior “self-care through caring for others” (volunteering based on self-development; helping a stranger to improve your own psychological well-being); conventional prosocial strategy “self-care” (self-isolation and preventive behavior). In the long run, it is necessary to identify personal and environmental resources that allowed people to effectively implement a prosocial self-isolation strategy during the COVID-19 pandemic, as well as various forms of volunteerism.